Canagliflozin-induced pancreatitis: a rare side effect of a new drug - Chowdhary M; Kabbani AA; Chhabra A (Therapeutics and Clinical Risk Management, 2015)
Mudit Chowdhary,1 Ahmad A Kabbani,1 Akansha Chhabra21Department of Internal Medicine, Mercer University School of Medicine, Macon, GA, USA; 2Department of Internal Medicine, New York University Langone Medical Center, New York, NY, USAAbstract: Acute pancreatitis is most commonly attributed to gallstones, alcohol abuse, and metabolic disorders such as hyperlipidemia and hypercalcemia. Medications are an infrequent yet commonly overlooked etiology of pancreatitis. Although several drugs have been implicated, antidiabetic agents are a rare cause for drug-induced pancreatitis. Canagliflozin is a new drug in the class of SGLT-2 inhibitors used for the treatment of type 2 diabetes mellitus. Serious reported side effects include renal impairment, hyperkalemia, and hypotension. Pancreatitis as a result of canagliflozin, however, is exceedingly rare. Here we describe a case of a 33-year old female who presented with severe acute pancreatitis in the setting of recent initiation of canagliflozin. Given the timing of her presentation and after excluding all other possible etiologies, it was determined that canagliflozin was the likely source of her illness. This case highlights the importance of identifying drug-induced pancreatitis, especially in novel drugs, as it is commonly neglected in patients with multiple medical comorbidities and those taking numerous medications. Prompt identification of drug-induced pancreatitis can improve management as well as decrease morbidity and mortality in these individuals.Keywords: canagliflozin, Invokana, pancreatitis, drug-induced pancreatitis, SGLT-2 inhibitor